2021
DOI: 10.3390/plants10112522
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol and Magnolol: Insights into Their Antidermatophytic Effects

Abstract: Dermatophyte infections represent a significant public health concern, with an alarming negative impact caused by unsuccessful therapeutic regimens. Natural products have been highlighted as a promising alternative, due to their long-standing traditional use and increasing scientific recognition. In this study, honokiol and magnolol, the main bioactives from Magnolia spp. bark, were investigated for their antidermatophytic activity. The antifungal screening was performed using dermatophyte standard strains and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Usually, synergistic (one drug enhances the activity of another), indifferent (drugs do not enhance each other activity), and antagonistic (one drug decreases the activity of another) interactions are defined by FICI ≤0.5, >0.5 -4.0, and > 4.0, respectively (Odds 2003). There are some studies that consider an extra type of interaction, namely "additive", when FICI value is between 0.5 and 1.0 (Trifan et al 2021). The combinatory antifungal activity may also be determined by adding a specific concentration of drug A to different concentrations of drug B, generally obtained by serial dilution.…”
Section: Methods Performed To Assess the Interaction Between Two Drugsmentioning
confidence: 99%
“…Usually, synergistic (one drug enhances the activity of another), indifferent (drugs do not enhance each other activity), and antagonistic (one drug decreases the activity of another) interactions are defined by FICI ≤0.5, >0.5 -4.0, and > 4.0, respectively (Odds 2003). There are some studies that consider an extra type of interaction, namely "additive", when FICI value is between 0.5 and 1.0 (Trifan et al 2021). The combinatory antifungal activity may also be determined by adding a specific concentration of drug A to different concentrations of drug B, generally obtained by serial dilution.…”
Section: Methods Performed To Assess the Interaction Between Two Drugsmentioning
confidence: 99%
“…Apigenin, rutin, and palmitic acid downregulated the expression of ERG11 [ 56 , 104 ]. Other studies targeted ergosterol biosynthesis by applying tormentic acid [ 105 ], benzodioxane derivatives [ 106 ], honokiol and magnolol [ 107 ], and cold atmospheric plasma [ 108 ].…”
Section: Recent Update On Antifungal Targets and Strategiesmentioning
confidence: 99%
“…Recently, it had been reported that honokiol inhibited the common standard strains and clinical strains of dermatophytes by destroying the ergosterol biosynthesis. And it enhanced the terbinafine's activity against Trichophyton rubrum 12 . Honokiol could also be used against other bacteria or viruses associating with skin diseases, for example, Propionibacterium acnes 13 and Herpes Simplex Virus‐1 14 …”
Section: The Therapeutic Applications In Dermatosismentioning
confidence: 99%